Pancasila In Islamic Perspective - Marzuki, Marzuki; Nur hajjiah Hasibuan; Salsabila Ayadi Fitri (Sean Institute, 2025)
Pancasila, US Indonesia's foundational philosophy, has a close relationship with Islamic teachings. This connection is evident in the alignment of Pancasila's principles with universal values of Islam. This study explores the relationship between Pancasila and Islam, the harmony of Islamic universal values with Pancasila, scholars' perspectives on Pancasila, and the challenges in applying Pancasila in the Islamic context in Indonesia. Findings suggest that Pancasila can be accepted as an inclusive state foundation, provided its implementation respect religious values and diversity. Therefore, Pancasila is note only compatible with Islam but also services US a unifying platform for English society.